2022
DOI: 10.1177/23259671221118836
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Affecting Return to Sports and Patient-Reported Outcomes After Opening-Wedge High Tibial Osteotomy in Active Patients

Abstract: Background: Although opening-wedge high tibial osteotomy (OWHTO) is favored for active patients who expect to return to sports, there is still a lack of robust evidence for factors affecting their recovery. Purpose: To identify (1) risk factors leading to a decreased level of return to preoperative sports after OWHTO and (2) patient characteristics and intraoperative factors influencing patient-reported outcomes after return to sports. Study Design: Case-control study; Level of evidence, 3. Methods: Included w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Under the same postoperative Lysholm knee score, patients with lower preoperative Lysholm knee score are better relieved from knee joint pain symptoms after surgery compared to those with higher preoperative Lysholm knee score, and have more confidence in returning to sports, thus enjoying a better chance promoting activity level. Katagiri et al[ 28 ] also discovered that high preoperative Tegner scores were a prognostic risk factor for not returning to preoperative sports levels after open-wedge high tibial osteotomy (OWHTO).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the same postoperative Lysholm knee score, patients with lower preoperative Lysholm knee score are better relieved from knee joint pain symptoms after surgery compared to those with higher preoperative Lysholm knee score, and have more confidence in returning to sports, thus enjoying a better chance promoting activity level. Katagiri et al[ 28 ] also discovered that high preoperative Tegner scores were a prognostic risk factor for not returning to preoperative sports levels after open-wedge high tibial osteotomy (OWHTO).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the results of this study suggest that preoperative and postoperative MPTA does not affect the improvement of postoperative sport activity level. A previous study suggested that a high postoperative MPTA was a prognostic risk factor for unsatisfactory outcomes in terms of returning to sports after OWHTO [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,23,24,27,31,40 Although satisfactory results have been reported in most patients undergoing MOWHTO, dissatisfactory results unexpectedly occur in a few patients. 5,14 Various factors have been reported to be associated with inferior outcomes after MOWHTO, including advanced age, greater body mass index, lower preoperative range of motion, and high-grade OA. 5,21,[28][29][30] A history of arthroscopic meniscectomy has been rarely reported in patients with OA knees undergoing MOWHTO.…”
mentioning
confidence: 99%